Evaluating Assessment Moderation: Towards Best Practice - Arthur, Christine Shobana * (2019)
Moderation of assessment is done to ensure consistency of marking across academicians, subjects, and programmes. The concerns that have always been raised by many academicians from the tertiary education setting are the difficulties of attaining consistency, the apprehensiveness of new academic members and the demanding nature of the assessment moderation process which increases the workload of academicians. Using a Theory of Change (Weiss, 1998), this paper provides a brief case-study description by evaluating the intended outputs, assumptions and activities of assessment moderation. In particular, this study aims to identify and depict the assessment moderation practice, elicit views on its effectiveness and assess the extent to which improvements can be attained in the higher education (HE) setting. The academic staff members of University A were interviewed to obtain their views and comments on their assessment moderation practice. The participants were selected based on the following characteristics: 1) Must have completed assessment moderation for at least 10 rounds (have at least 5 years and above of experience in moderation), 2) Must have carried out assessment moderation once or twice (have less than one year of experience). The outcome of this study challenges University A to improve its assessment moderation practice by introducing other relevant and suitable methods of moderation. The paper also proposes applicable solutions for the institution to address the lack of training and support amongst new academic staff members and parttimers. The need for establishing better coordination between moderators and markers as well as establishing a formal buddy system were highlighted in this case study. This paper empahsises continous quality improvement at the HE setting because universities allow for substantial discretions and local adaptation (Weick, 1995). All in all, this study adds further weight to the existing body of literature on moderation practices in HE institutions.